Glass-ceramics, preparation method, glass-ceramics products and electronic equipment

By introducing alkali metal and alkaline earth metal components into the calcium-aluminum binary system, high mechanical strength microcrystalline glass is prepared, which solves the problem of insufficient anti-fall and scratch resistance of existing glasses, and reduces the melting temperature of glass and Energy consumption.

CN117430332BActive Publication Date: 2025-01-07HONOR DEVICE CO LTD +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202210822084.1
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-07-12
Publication Date
2025-01-07
Estimated Expiration
2042-07-12

AI Technical Summary

Technical Problem

The mechanical strength of existing glass cannot meet users' high requirements for anti-fall and scratch resistance of electronic equipment.

Method used

By introducing alkali metals and alkaline earth metals into the calcium-aluminum binary system, the glass-forming performance of microcrystalline glass is improved, and the glass-forming area of ​​calcium-aluminum glass is expanded, and microcrystalline glass with higher mechanical strength is prepared. The microcrystalline glass includes components such as Al2O3, CaO, alkaline earth metal oxide, alkali metal oxide, B2O3 and Sb2O3, and improves hardness through nanocrystalline particles.

Benefits of technology

It achieves higher anti-fall and scratch resistance of microcrystalline glass, and reduces the melting temperature of the glass and reduces energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117430332B_ABST
    Figure CN117430332B_ABST
Patent Text Reader

Abstract

The present application provides a glass-ceramic, a preparation method, a glass-ceramic product and an electronic device, which belongs to the technical field of glass-ceramic preparation, wherein the glass-ceramic includes the following components in terms of molar percentage of oxides: Al2O3: 30%-55%; CaO: 25%-55%; alkaline earth metal oxides: 8%-20%; alkali metal oxides: 3%-15%; B2O3: 0%-10%; and Sb2O3: 0%-1%. The glass-ceramic according to the embodiment of the present application can effectively improve its glass-forming properties while maintaining a high mechanical strength of the glass-ceramic, and reduce the glass melting temperature and energy consumption by incorporating alkaline earth metal ions and alkali metal ions into the glass system composed of calcium aluminum.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the technical field of microcrystalline glass preparation, and in particular to microcrystalline glass, a preparation method, microcrystalline glass products and electronic equipment. Background Art

[0002] In recent years, with the rapid development of electronic devices, people have higher and higher requirements for the drop resistance of electronic devices. Take mobile phones as an example. As the size of mobile phone screens continues to increase, mobile phone covers are also getting larger and larger, and the use of 3D glass is gradually increasing, consumers have higher requirements for glass's drop resistance and scratch resistance. Therefore, a microcrystalline glass with higher mechanical properties is needed to meet user needs. Summary of the invention

[0003] In view of this, the present application provides a microcrystalline glass, a preparation method, a microcrystalline glass product and an electronic device to provide a microcrystalline glass that is more resistant to falling and scratching, thereby solving the problem that the mechanical strength of existing glass cannot meet user needs.

[0004] Some embodiments of the present application provide a glass-ceramic. The present application is introduced from multiple aspects below, and the embodiments and beneficial effects of the following aspects can be referenced to each other.

[0005] In a first aspect, the present application provides a glass-ceramic, which comprises the following components, measured by mole percentage of oxides:

[0006] Al2O3: 30%-55%;

[0007] CaO: 25%-55%;

[0008] Alkaline earth metal oxides: 8%-20%;

[0009] Alkali metal oxides: 3%-15%;

[0010] B2O3: 0%-10%; and

[0011] Sb2O3: 0%-1%.

[0012] According to the glass-ceramics of the embodiment of the present application, during the preparation process of the glass-ceramics, by introducing components such as alkali metals and alkaline earth metals into the calcium-aluminum binary system, its glass-forming properties can be improved, and the glass-forming region of the calcium-aluminate glass can be expanded to obtain the calcium-aluminate glass. The calcium-aluminate glass has higher mechanical strength, and its drop resistance and scratch resistance are higher than those of the traditional silicate glass and the high-aluminate glass. At the same time, the glass melting temperature is reduced, thereby reducing energy consumption.

[0013] As an embodiment of the first aspect of the present application, the alkaline earth metal oxide includes one or more of MgO, SrO and BaO.

[0014] As an embodiment of the first aspect of the present application, the alkaline earth metal oxide includes at least two of MgO, SrO and BaO, and the content of each alkaline earth metal ion is 2%-10% by mole percentage. By adding the alkaline earth metal of this component, the glass-forming property of the calcium-aluminum binary system can be effectively improved, and the hardness of the microcrystalline glass can be improved.

[0015] As an embodiment of the first aspect of the present application, the alkali metal oxide includes one or more of Li2O, Na2O and K2O.

[0016] As an embodiment of the first aspect of the present application, the alkali metal oxide comprises, in terms of molar percentage of each component: Li2O: 1%-10%; Na2O: 2%-10%; and K2O: 0-10%. This composition ratio further improves the glass-forming performance of the calcium-aluminum binary system.

[0017] As an embodiment of the first aspect of the present application, the microcrystalline glass includes nanocrystalline particles, and the nanocrystalline particles can be one or more crystal phases of CaAl2O4, MgAl2O4 and SrAl2O4.

[0018] As an embodiment of the first aspect of the present application, the average particle size of the nanocrystalline particles is 1-100 nm.

[0019] As an embodiment of the first aspect of the present application, the content of nano-microcrystalline particles accounts for more than 50% of the total amount of the microcrystalline glass.

[0020] As an embodiment of the first aspect of the present application, the average particle size of the nano-microcrystalline particles is 1-50nm, and the content of the nano-microcrystalline particles accounts for more than 80% of the total amount of the microcrystalline glass. The increase in the content of the nano-microcrystalline particles can effectively improve the hardness of the microcrystalline glass.

[0021] As an embodiment of the first aspect of the present application, the Vickers hardness of the microcrystalline glass is between 8.4-9.1 GPa.

[0022] As an embodiment of the first aspect of the present application, the Young's modulus of the microcrystalline glass is between 110-129 GPa.

[0023] In a second aspect, the present application also provides a method for preparing microcrystalline glass, comprising:

[0024] Weighing raw materials, wherein the raw materials, in terms of molar percentage of oxides, have the following components: Al2O3: 30%-55%, CaO: 25%-55%, alkaline earth metal oxides: 8%-20%, alkali metal oxides: 3%-15%, B2O3: 0%-10%, and Sb2O3: 0%-1%;

[0025] Grinding the symmetrically taken raw materials to obtain mixed powder;

[0026] The mixed powder is melted to obtain glass liquid;

[0027] pouring glass liquid to obtain a glass precursor;

[0028] The glass precursor is annealed to obtain glass-ceramics.

[0029] According to the preparation method of the glass-ceramics of the embodiment of the present application, by introducing alkali metals and alkaline earth metals and other components into the calcium-aluminum binary system, its glass-forming properties can be improved, and the glass-forming region of the calcium-aluminate glass can be expanded to obtain the calcium-aluminate glass. The calcium-aluminate glass has higher mechanical strength, and its drop resistance and scratch resistance are higher than those of the traditional silicate glass and high-aluminate glass. At the same time, the glass melting temperature is reduced, thereby reducing energy consumption.

[0030] As an embodiment of the second aspect of the present application, the mixed powder is melted to obtain glass liquid, including:

[0031] The mixed powder is placed in a crucible, and the crucible is placed in a furnace, and melted at 1400-1600°C for 1-3 hours to obtain glass liquid.

[0032] As an embodiment of the second aspect of the present application, pouring glass liquid to obtain a glass precursor includes:

[0033] The glass liquid is poured onto the preheated mold to obtain a uniform glass precursor.

[0034] As an embodiment of the second aspect of the present application, a glass precursor is annealed and cooled to room temperature to obtain a glass-ceramic, comprising:

[0035] The glass precursor is transferred to a muffle furnace for annealing. The temperature of the muffle furnace is lowered to between 30-50°C below the glass transition temperature for 3-8 hours. The temperature is lowered in steps at a cooling rate of 0.1-10°C / h, and each temperature is kept for 3-8 hours until it is cooled to room temperature to obtain microcrystalline glass.

[0036] As an embodiment of the second aspect of the present application, the Al2O3 is introduced as Al2O3 or Al(OH)3, the CaO is introduced as CaCO3, the alkaline earth metal oxide is introduced as alkaline earth metal carbonate, the alkali metal oxide is introduced as alkali metal carbonate, and the B2O3 is introduced as B(OH)3. As an embodiment of the second aspect of the present application, the alkaline earth metal carbonate includes one or more of MgCO3, SrCO3 and BaCO3.

[0037] As an embodiment of the second aspect of the present application, the carbonate of alkaline earth metals includes MgCO3, SrCO3 and BaCO3, and the content of each alkaline earth metal ion is 2%-10% by mole percentage. By adding the alkaline earth metal of this component, the glass-forming property of the calcium-aluminum binary system can be effectively improved, the hardness of the microcrystalline glass can be improved, and the glass melting temperature and energy consumption can be reduced.

[0038] As an embodiment of the second aspect of the present application, the carbonate of alkali metal includes one or more of Li2CO3, Na2CO3 and K2CO3. The alkaline earth metal of this component can effectively improve the glass-forming property of the calcium-aluminum binary system and improve the hardness of the microcrystalline glass.

[0039] As an embodiment of the second aspect of the present application, the molar percentages of the components, calculated as alkali metal oxides, are: Li2O: 1%-10%; Na2O: 2%-10%; and K2O: 0-10%.

[0040] In a third aspect, the present application further provides a glass-ceramic product, wherein the glass-ceramic product is made of the glass-ceramic described in any one of the first aspect and its embodiments.

[0041] In a fourth aspect, the present application further provides an electronic device, including:

[0042] Main body middle frame;

[0043] A cover plate, the cover plate being arranged on one side of the main body middle frame; and

[0044] A display screen, the display screen being arranged on a side of the main body middle frame opposite to the cover plate;

[0045] Wherein, at least one of the cover plate and the display screen comprises the microcrystalline glass described in any one of the aforementioned first aspect and its embodiments. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 A schematic diagram of the structure of a mobile phone according to an embodiment of the present application;

[0047] Figure 2a An exploded view of a mobile phone structure according to an embodiment of the present application;

[0048] Figure 2b Another structural schematic diagram of a mobile phone according to an embodiment of the present application;

[0049] Figure 3 This is a scanning electron microscope photo of the microscopic morphology of the glass-ceramics of one embodiment of the present application;

[0050] Figure 4 A transmittance curve diagram of a glass-ceramic according to an embodiment of the present application;

[0051] Figure 5 This is a flow chart of a method for preparing glass-ceramics according to one embodiment of the present application. DETAILED DESCRIPTION

[0052] The following will provide a clear and complete description of the various embodiments of the present application in conjunction with the accompanying drawings.

[0053] Nanocrystal glass, also known as ceramic glass, is an inorganic non-metallic material. It is a new type of material that has both glass and ceramic properties. The atomic arrangement inside ordinary glass is irregular, which is one of the reasons why glass is fragile. Nanocrystal glass, like ceramics, contains crystals, and the atomic arrangement of the crystals is regular. Therefore, nanocrystal glass is brighter than ceramics and tougher than glass.

[0054] In order to facilitate understanding of the technical solution of the present application, the technical problem of the present application is first described below.

[0055] Calcium aluminate glass is a type of glass-ceramic, and has better mechanical properties than traditional glass. However, the glass-forming region of the calcium-aluminum binary system is very limited, and it can only be glass-formed when the CaO content is in the range of 61-66 mol%, which makes the glass-forming performance of conventional calcium-aluminate glass low, affecting the application of this system of glass.

[0056] In order to solve the above technical problems, the present application provides a microcrystalline glass. By introducing alkali metals and alkaline earth metals and other components into the glass of the calcium-aluminum binary system during the preparation of microcrystalline glass, the glass-forming properties of the microcrystalline glass are improved, and the glass-forming region of the calcium-aluminate glass is expanded, thereby obtaining the microcrystalline glass provided by the present application. The microcrystalline glass provided by the present application has higher mechanical strength, and its drop resistance and scratch resistance are higher than those of traditional glass.

[0057] The microcrystalline glass of the present application can be applied to electronic devices. For example, the microcrystalline glass can be manufactured into cover plates of electronic devices, such as the front cover glass, rear cover (back plate), etc. of mobile phone screens, as well as housings, etc.

[0058] The following uses the application of microcrystalline glass in mobile phones as an example to illustrate the application scenarios of the microcrystalline glass in the embodiments of the present application.

[0059] refer to Figure 1 , Figure 1 The schematic diagram of the structure of a mobile phone in an embodiment of the present application is shown. Figure 1 As shown, the mobile phone 100 may include a back cover, a display screen, a main body frame, a camera protection cover, etc. Some or all of these components may be made of microcrystalline glass.

[0060] refer to Figure 2a , Figure 2a An exploded view of the structure of a mobile phone according to an embodiment of the present application is shown. Figure 2a As shown, the mobile phone 100 may include a main body frame 10, a back cover 20 and a display screen 30, wherein the back cover 20 and the display screen 30 are respectively arranged on both sides of the main body frame 10 to cover the components arranged inside the frame. The display screen 30 and / or the back cover 20 may be made of microcrystalline glass. In the embodiment of the present invention, the display screen 30 and / or the back cover 20 may be made of microcrystalline glass in its entirety or only partially. In the embodiment of the present invention, the display screen 200 may be a touch display screen.

[0061] In one embodiment of the present application, Figure 2b Another schematic diagram of the structure of a mobile phone in an embodiment of the present application is shown. A camera protection cover 21 is provided on the back cover 20 of the mobile phone 100. The camera protection cover 21 is used to cover the camera assembly to better protect the camera assembly. Among them, all or part of the camera protection cover can be made of the microcrystalline glass of the present application. In the embodiment of the present application, the camera protection cover is not limited to Figure 2a The form shown in .

[0062] The mobile phone of the present application adopts microcrystalline glass with excellent anti-drop performance, so that the mobile phone has the properties of drop resistance and scratch resistance, which can improve the reliability of the terminal product and enhance the user experience.

[0063] In some embodiments of the present application, the electronic device may also be a laptop computer, a tablet computer, a desktop computer, or other electronic device, or may be a smart wearable device such as a watch or a bracelet, etc. The present application does not limit the type of electronic device.

[0064] In some embodiments, microcrystalline glass can also be applied to other scenarios. For example, glass parts can be used in vehicles, such as headlight covers, windshields, or dashboard glass inside the car, which can be made of the microcrystalline glass of the present application.

[0065] In some embodiments, the microcrystalline glass can also be processed into glass products with different dimensions for use in different devices, for example, 2D, 2.5D or 3D glass products. The present application does not limit the application of microcrystalline glass and the form of glass products.

[0066] The glass-ceramics of the embodiment of the present application will be described in detail below with reference to the accompanying drawings.

[0067] In the embodiments of the present application, the glass-ceramics includes the components shown in Table 1 in terms of molar percentage of oxides:

[0068] Serial number Components mol% 1 <![CDATA[Al2O3]]> 30-55 2 CaO 25-55 3 Alkaline earth metal oxides 8-20 4 Alkali metal oxides 3-15 5 <![CDATA[B2O3]]> 0-10 6 <![CDATA[Sb2O3]]> 0-1

[0069] Table 1

[0070] In an embodiment of the present application, in a glass system containing Al2O3 and CaO, alkaline earth metal ions, such as magnesium oxide (MgO), strontium oxide (SrO), barium oxide (BaO), etc., are added to improve the glass forming ability. Glass itself is an amorphous material. When high field strength cations, such as Mg ions, are added, they will attract the vacant oxygen atoms in the glass network to form a variety of tetrahedral or hexahedral structures, making the network structure tend to be tight and easier to form glass. Among them, magnesium oxide (MgO) has a more complex structure in glass, and the coordination form in the glass network usually changes with the alkali metal content. Among them, the five- and six-coordinated Mg in the glass network has a similar effect to the alkali metal, and mainly plays a role in destroying the glass network structure. However, the four-coordinated Mg exists in the glass as a [MgO4] structural unit, which can enhance the connection between the glass network formers. Strontium oxide (SrO) has important biological activity and can improve the compatibility of glass with biological cells in bioglass. Barium oxide (BaO) can mainly increase the refractive index and optical absorption of glass, and can also reduce the melting temperature of glass.

[0071] In a glass system containing Al2O3 and CaO, adding alkali metal ions can reduce the glass melting viscosity layer and improve the glass forming ability. Among them, Li2O, Na2O, and K2O are network exosomes that can reduce the glass melting viscosity layer and promote rapid melting and clarification of the glass. In addition, Li2O and Na2O are one of the necessary components, which is to make the glass contain enough Li + 、Na + Respectively with Na in molten potassium salt + , K + An exchange occurs, producing high compressive stress on the glass surface.

[0072] In addition, adding alkaline earth metal ions and alkali metal ions to the glass system of Al2O3 and CaO can form a mixed cation effect in the original calcium aluminate glass, including mixed alkali effect and mixed alkaline earth effect. The generation of mixed cation effect can effectively improve the glass forming properties and reduce the melting temperature and melting energy consumption of glass.

[0073] In the embodiments of the present application, the microcrystalline glass obtained by proportioning the components according to the component contents in Table 1 can effectively improve the glass-forming properties of the glass, expand the glass-forming area of ​​the calcium aluminate glass, generate strong compressive stress on the glass surface, and improve the mechanical strength of the microcrystalline glass. Its drop resistance and scratch resistance are higher than those of traditional microcrystalline glass, and the glass melting temperature and energy consumption can be reduced.

[0074] In one embodiment of the present application, the alkaline earth metal oxide includes one or more of MgO, SrO and BaO. The alkaline earth metal oxide includes at least two of MgO, SrO and BaO, and the content of each alkaline earth metal ion is 2%-10% in molar percentage. This ratio can expand the glass-forming region of the calcium-aluminum binary system, thereby improving the glass-forming ability, which is beneficial to improving the mechanical properties of the microcrystalline glass.

[0075] In the embodiments of the present application, MgO may be introduced as MgCO3, SrO may be introduced as SrCO3, and BaO may be introduced as BaCO3. In some embodiments, the above alkaline earth metal oxides may be introduced in other ways, such as by introducing the metal oxides themselves, such as directly introducing MgO, SrO and BaO. The present application does not limit the introduction form of the metal oxides.

[0076] In another embodiment of the present application, the alkali metal oxide includes one or more of Li2O, Na2O and K2O. The molar percentages of the components in the alkali metal oxide may be: the molar percentage of Li2O is between 1% and 10%. In one embodiment of the present application, the molar percentage of Li2O may be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%, etc., the molar percentage of Na2O is between 2% and 10%, for example, it may be 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%, etc., and the molar percentage of K2O is between 0% and 10%, for example, it may be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%, etc.

[0077] refer to Figure 3 , Figure 3 The scanning electron microscope photo of the microstructure of the glass-ceramics of the embodiment of the present application is shown. Figure 3 As shown, after the microcrystalline glass having the above components is heat-treated at different times and temperatures, the nanocrystalline particles shown in the figure can be obtained. The nanocrystalline particles can be one or more crystalline phases of CaAl2O4, MgAl2O4 and SrAl2O4. Among them, the particle size of the nanocrystalline particles can be from a few nanometers to hundreds of nanometers. In an embodiment of the present application, the average particle size of the nanocrystalline particles is 1-100nm, and the content of nanocrystalline can account for more than 50% of the entire microcrystalline glass. In another embodiment of the present application, the average particle size of the nanocrystalline is 1-50nm, and the content of nanocrystalline can account for more than 80% of the entire microcrystalline glass, thereby greatly improving the strength of the microcrystalline glass.

[0078] In one embodiment of the present application, the glass may be a transparent glass material after microcrystallization. Figure 1The cover glass of the mobile phone shown in the figure can not only improve the anti-drop performance of the mobile phone cover, but also have a high transmittance. Figure 2b The camera protection cover shown can make the camera protection cover resistant to falling and have high transmittance, thereby better meeting the camera's demand for light transmission.

[0079] refer to Figure 4 , Figure 4 FIG. 2 shows a transmittance curve of the microcrystalline glass of the embodiment of the present application. Figure 4 As shown, the transmittance of the microcrystalline glass of the present application can reach more than 90% in the visible light range, which can meet the optical requirements of display and shooting of electronic devices and is suitable for making electronic device display screen cover plates and camera protection cover plates.

[0080] In some embodiments, glass can also be a non-transparent material after microcrystallization. Non-transparent materials can be used to make Figure 1 The back panel of the mobile phone is shown.

[0081] In an embodiment of the present application, a transparent glass material or a non-transparent glass material can be obtained by adjusting the components in the entire glass system. For example, when preparing a transparent glass material, 0-1 mol% Sb2O3 can be added during the preparation of microcrystalline glass, for example, 0.1 mol%, 0.2 mol%, 0.3 mol%, 0.4 mol%, 0.5 mol%, 0.6 mol%, 0.7 mol%, 0.8 mol%, 0.9 mol% or 1 mol%, etc., and the heat treatment temperature and time are adjusted to obtain a transparent glass material. When preparing a non-transparent glass material, Sb2O3 may not be added, and the heat treatment temperature and time may be appropriately adjusted to obtain a non-transparent glass material.

[0082] In the embodiments of the present application, B2O3 in the calcium aluminate glass serves as a network former of the base glass. In the embodiments of the present application, the content of B2O3 may be 1 mol%, 2 mol%, 3 mol%, 4 mol%, 5 mol%, 6 mol%, 7 mol%, 8 mol%, 9 mol% or 10 mol%, and this ratio can reduce the viscosity of the glass, facilitate the production of the glass, and change its glass-forming properties.

[0083] In some embodiments, in order to further improve the hardness of the glass-ceramics, the glass-ceramics may be subjected to low-temperature chemical strengthening (ion exchange chemical strengthening) after the glass-ceramics are obtained to obtain strengthened glass-ceramics. For example, the glass-ceramics may be immersed in a bath of an ion exchange solution, the ion exchange solution may be sprayed onto the glass-ceramics, or the ion exchange solution may be physically applied to the glass-ceramics by any other means so that the glass-ceramics are in contact with the ion exchange solution. By subjecting the glass-ceramics to ion exchange chemical strengthening, a compressive stress layer may be formed on the surface of the glass-ceramics, so that the mechanical properties of the strengthened glass-ceramics are further improved.

[0084] In some embodiments, ion exchange chemical strengthening can be divided into multiple strengthening steps. For example, when chemical strengthening is performed twice, the temperature and time of each time can be adjusted according to different needs, thereby further improving the ion exchange depth and surface compressive stress, thereby improving the mechanical properties of the microcrystalline glass.

[0085] The preparation method of the microcrystalline glass of the present application is described below with reference to specific embodiments.

[0086] refer to Figure 5 , Figure 5 FIG. 1 is a flow chart showing a method for preparing glass-ceramics according to an embodiment of the present application. Figure 5 As shown, the preparation method includes S510-S540.

[0087] S510, weigh the raw materials.

[0088] In an embodiment of the present application, the raw materials may include Al2O3 or Al(OH)3, CaCO3, carbonates of alkaline earth metals, carbonates of alkali metals, B(OH)3 and Sb2O3 raw materials. Among them, Al(OH)3 is introduced as the form of Al2O3, CaCO3 is introduced as the form of CaO, and B(OH)3 is introduced as the form of B2O3. Among them, the addition amount of each component of the raw material is calculated as the molar percentage of the oxide, respectively, Al2O3: 30%-55%, for example, it can be 30%, 35%, 40%, 45%, 50% or 55%; CaO: 25%-55%, for example, 25%, 30%, 35%, 45%, 50% or 55%; Alkaline earth metal oxide: 8%-20%, for example, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%. 20%; alkali metal oxides: 3%-15%, for example, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14% or 15%; B2O3: 0%-10%, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%; Sb2O3: 0%-1%, for example, 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, 0.6%, 0.7%, 0.8%, 0.9% or 1%.

[0089] In the present application, defects in the glass can be eliminated by adding Sb2O3, making the glass colorless and transparent, improving the brown color problem of calcium aluminate glass, and making the glass have better transmittance, which can meet the optical requirements of display and shooting of electronic devices.

[0090] In the embodiments of the present application, adding B2O3 within 10% as defined in the present application can effectively change the glass-forming properties of the entire glass system and appropriately reduce the viscosity of the glass, thereby solving the problem of processing being affected by excessive viscosity.

[0091] In one embodiment of the present application, the carbonate of alkaline earth metal can be one or more of MgCO3, SrCO3 and BaCO3. That is to say, the carbonate of alkaline earth metal is taken as the introduction form of alkaline earth metal oxide. Wherein, when the alkaline earth metal oxide includes more than two components, the content of each alkaline earth metal ion is measured in terms of oxide molar percentage, accounting for 2%-10% of the total amount of raw materials, for example, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%. The total amount of alkaline earth metal oxide accounts for 8%-20% of the total amount of raw materials. Such a ratio can enhance the connection between the glass network formers, thereby improving the mechanical properties of the microcrystalline glass, and can improve the refractive index, optical absorption, etc. of the glass, reduce the glass melting temperature, and thus reduce the melting energy consumption.

[0092] In one embodiment of the present application, the alkali metal oxide includes one or more of Li2O, Na2O and K2O. When there are multiple alkali metal oxides, the percentage of each metal ion oxide in the total amount of raw materials is: Li2O 1%-10%, such as 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%; Na2O 2%-10%, such as 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%; and K2O 0-10%, such as 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9% or 10%, and the total content of alkali metal oxides accounts for 3%-15% of the total amount of raw materials. This ratio can reduce the glass melting viscosity layer, promote rapid melting and clarification of glass, generate high compressive stress on the glass surface, and improve mechanical properties.

[0093] S520, grinding the symmetrically taken raw materials to obtain a mixed powder.

[0094] The weighed raw materials are mixed and fully ground to form a mixed powder.

[0095] S530, melting the mixed powder to obtain molten glass.

[0096] In the embodiment of the present application, the mixed powder can be placed in a crucible, and the crucible is placed in a furnace and melted at a temperature of 1400-1600°C for 1-3 hours to obtain glass liquid. The melting temperature can be 1410°C, 1450°C, 1500°C, 1550°C or 1600°C, etc. The melting time can be 1 hour, 1.5 hours, 2 hours, 2.5 hours or 3 hours.

[0097] S540, pouring glass liquid to obtain a glass precursor.

[0098] In the embodiments of the present application, the molten glass can be poured onto a preheated mold to avoid excessive temperature differences that affect the glass-forming effect, thereby obtaining a transparent and uniform glass precursor.

[0099] S550, annealing the glass precursor to obtain glass-ceramics.

[0100] In one embodiment of the present application, the glass precursor is transferred to a muffle furnace for annealing treatment, the annealing temperature is 30-50°C below the glass transition temperature (Tg), after being kept warm for 3-8 hours, the temperature is stepped down at a cooling rate of 0.1-10°C / h, each temperature is kept warm for 3-8 hours, and then cooled to room temperature to obtain microcrystalline glass. The microcrystalline glass is processed to obtain a glass product. For example, the taken out microcrystalline glass can be processed into a glass sheet product with a thickness of 0.5-1 mm.

[0101] In one embodiment of the present application, the cooling rate can be 0.5℃ / h, 1℃ / h, 1.5℃ / h, 2℃ / h, 3℃ / h, 4℃ / h, 5℃ / h, 6℃ / h, 7℃ / h, 8℃ / h, 9℃ / h or 10℃ / h, etc.

[0102] It should be noted that when describing the microcrystalline glass above, the example ratios of the chemical components and the reasons why each chemical component can improve the glass-forming properties and mechanical properties of the microcrystalline glass have been described in detail. Please refer to the specific description of the above microcrystalline glass for details, and no further details will be given here.

[0103] In addition, the steps and methods not mentioned in this application may adopt the methods of the prior art, and this application will not describe them in detail.

[0104] The performance indicators of the microcrystalline glass in the embodiments of the present application are explained below in conjunction with specific embodiments.

[0105] The implementation steps of the specific embodiment are as follows, and the specific parameter values ​​can be referred to Table 2:

[0106] 1) Weigh the raw materials. Weigh the raw materials according to the molar percentage of the metal oxides shown in Table 2.

[0107] 2) The weighed raw materials are mixed uniformly, melted at 1600° C. for 2 hours, then cast into shape, annealed at 700° C. for 5 hours, and then cooled to room temperature at a cooling rate of 1° C. per minute to obtain calcium aluminate glass.

[0108] 3) The obtained glass precursor was processed into a glass sheet of 10 mm × 10 mm × 1 mm and polished on both sides.

[0109] 4) The calcium aluminate glass is subjected to heat treatment for microcrystallization (the heat treatment conditions of each embodiment are shown in Table 2). The Vickers hardness and Young's modulus of the glass after the heat treatment are respectively listed in Table 2.

[0110] 5) The heat-treated glass sheet is further strengthened by ion exchange. The ion exchange conditions are shown in Table 2, and the Vickers hardness of the strengthened calcium aluminate glass-ceramics is shown in Table 2. The first ion exchange in Table 2 includes: ion exchange the heat-treated glass in molten potassium salt.

[0111] In an embodiment, the molten potassium salt may be potassium nitrate, and the temperature of the ion exchange is 350°C-600°C, and the time is 0.5-3 hours. The secondary ion exchange includes: subjecting the heat-treated glass to a first ion exchange in a first molten salt, and then subjecting it to a second ion exchange in a second molten salt. The first molten salt is a mixed molten salt of potassium nitrate and sodium nitrate, and the temperature of the first ion exchange is 350-600°C, and the time is 0.5-3h; the second molten salt is potassium nitrate, and the temperature of the second ion exchange is 350-600°C, and the time is 0.5-3h.

[0112] Table 2 below is a table of parameter data corresponding to 7 different embodiments using the above implementation steps.

[0113]

[0114]

[0115] Table 2

[0116] It can be seen from Table 2 that the microcrystalline glass of the embodiment of the present application has relatively high Vickers hardness and Young's modulus, with the Vickers hardness being between 8.4 and 9.1 GPa and the Young's modulus being between 110 and 129 GPa.

[0117] Among them, the test standard of Vickers hardness adopts the method in national standard GB / T 37900-2019, in which the pressure is 0.1kgf and the pressure is maintained for 10s. The test of Young's modulus refers to the method in national standard GB / T 7962.6-2010.

[0118] In addition, the hardness of the microcrystalline glass in the present application is compared with that of the traditional silicate glass in the prior art. The same test method is used and conventional commercial microcrystalline glass is used as a comparative example. The Vickers hardness of the glass after chemical strengthening in the comparative example is 6.3 GPa and the Young's modulus is 100 GPa.

[0119] From the test results of the microcrystalline glass in Table 2 and the comparative example, it can be seen that the microcrystalline glass obtained according to the microcrystalline glass preparation method of the embodiment of the present application has a higher Vickers hardness and Young's modulus, and its Vickers hardness is between 8.4-9.1GPa, and its Young's modulus is between 110-129GPa, which are much higher than the Vickers hardness and Young's modulus of the glass in the prior art.

[0120] Although the present application has been illustrated and described with reference to certain preferred embodiments thereof, it will be apparent to those skilled in the art that various changes in form and details may be made therein without departing from the spirit and scope of the present application.

Claims

1. A glass-ceramic, characterized in that: The microcrystalline glass comprises the following components in terms of molar percentage of oxides: Al2O3: 30%-55%; CaO: 25%-55%; Alkaline earth metal oxide: 8%-20%, wherein the alkaline earth metal oxide includes one or more of MgO, SrO and BaO; Alkali metal oxides: 3%-15%; B2O3: 0%-10%; and Sb2O3: 0%-1%; The Al2O3, CaO, alkaline earth metal oxide, alkali metal oxide, B2O3 and Sb2O3 are used to obtain a glass precursor through melting and casting, and the glass precursor is transferred to a muffle furnace for annealing. The annealing treatment reduces the temperature of the muffle furnace to between 30-50°C below the glass transition temperature, and keeps it warm for 3-8h, and cools it stepwise at a cooling rate of 0.1-10°C / h, and keeps each temperature for 3-8h until it cools to room temperature, thereby obtaining the microcrystalline glass containing nano-microcrystalline particles. The average particle size of the nano-microcrystalline particles is 1-50 nm, the nano-microcrystalline particles include one or more crystal phases of CaAl2O4, MgAl2O4 and SrAl2O4, and the content of the nano-microcrystalline particles accounts for more than 80% of the total amount of the entire microcrystalline glass.

2. The glass-ceramic according to claim 1, characterized in that: The alkaline earth metal oxides include at least two of MgO, SrO and BaO, and the content of each alkaline earth metal ion is 2%-10% in molar percentage.

3. The glass-ceramic according to claim 2, characterized in that: The alkali metal oxide includes one or more of Li2O, Na2O and K2O.

4. The glass-ceramic according to claim 3, characterized in that: In terms of mole percentage of each component, the alkali metal oxide comprises: Li2O: 1%-10%; Na2O: 2%-10%; and K2O: 0-10%.

5. The glass-ceramics according to any one of claims 1 to 4, characterized in that: The Vickers hardness of the microcrystalline glass is between 8.4-9.1 GPa.

6. The glass-ceramics according to any one of claims 1 to 4, characterized in that: The Young's modulus of the glass-ceramics is between 110-129 GPa.

7. A method for preparing glass-ceramics, characterized in that: include: Weighing raw materials, wherein the raw materials, in terms of molar percentage of oxides, are composed of 30%-55% Al2O3, 25%-55% CaO, 8%-20% alkaline earth metal oxides, 3%-15% alkali metal oxides, 0%-10% B2O3, and 0%-1% Sb2O3, wherein the alkaline earth metal oxides include one or more of MgO, SrO, and BaO; Grinding the symmetrically taken raw materials to obtain a mixed powder; Melting the mixed powder to obtain molten glass; pouring the glass liquid to obtain a glass precursor; The glass precursor is transferred to a muffle furnace for annealing treatment, wherein the temperature of the muffle furnace is lowered to between 30-50°C below the glass transition temperature, and kept warm for 3-8 hours, and the temperature is lowered stepwise at a cooling rate of 0.1-10°C / h, and each temperature is kept warm for 3-8 hours until it is cooled to room temperature to obtain the microcrystalline glass containing nano-microcrystalline particles. The average particle size of the nano-microcrystalline particles is 1-50 nm, the nano-microcrystalline particles include one or more crystal phases of CaAl2O4, MgAl2O4 and SrAl2O4, and the content of the nano-microcrystalline particles accounts for more than 80% of the total amount of the entire microcrystalline glass.

8. The method according to claim 7, characterized in that The mixed powder is melted to obtain glass liquid, comprising: The mixed powder is placed in a crucible, and the crucible is placed in a furnace to melt at 1400-1600° C. for 1-3 hours to obtain glass liquid.

9. The method according to claim 7, characterized in that: Casting the glass liquid to obtain a glass precursor comprises: The glass liquid is poured on a preheated mold to obtain a uniform glass precursor.

10. The method according to claim 7, characterized in that The Al2O3 is introduced as Al2O3 or Al(OH)3, the CaO is introduced as CaCO3, the alkaline earth metal oxide is introduced as alkaline earth metal carbonate, the alkali metal oxide is introduced as alkali metal carbonate, and the B2O3 is introduced as B(OH)3.

11. The method according to claim 10, characterized in that The carbonates of alkaline earth metals include one or more of MgCO3, SrCO3 and BaCO3.

12. The method according to claim 11, characterized in that The alkaline earth metal carbonates include MgCO3, SrCO3 and BaCO3, and the content of each alkaline earth metal ion, measured in molar percentage of oxide, accounts for 2%-10% of the total raw material.

13. The method according to any one of claims 10 to 12, characterized in that: The alkali metal carbonate includes one or more of Li2CO3, Na2CO3 and K2CO3.

14. The method according to claim 13, characterized in that Calculated as alkali metal oxides, the molar percentages of the components are: Li2O: 1%-10%; Na2O: 2%-10%; and K2O: 0-10%.

15. A glass-ceramic product, characterized in that: The microcrystalline glass product is made of the microcrystalline glass described in any one of claims 1-6.

16. An electronic device, characterized in that: include: Main body middle frame; A cover plate, the cover plate being arranged on one side of the main body middle frame; as well as A display screen, the display screen being arranged on a side of the main body middle frame opposite to the cover plate; Wherein, at least one of the cover plate and the display screen comprises the microcrystalline glass according to any one of claims 1-6.